2021
DOI: 10.37887/ej.v1i4.16606
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Yang Berhubungan Dengan Tingkat Kecemasan Di Masa Pandemi Covid-19 Pada Mahasiswa Universitas Halu Oleo

Abstract: AbstrakKecemasan merupakan kondisi emosional yang ditandai dengan kekhawatiran yang berlebihan terhadap berbagaiperistiwa kehidupan sehari hari. Kecamasan di tengah pandemi Covid-19 yang berpotensi terus meningkat danmenjadi suatu ancaman terhadap kondisi kesehatan mental masyarakat di seluruh dunia. Mahasiswa rentan terhadapkecemasan, keadaan dapat menyebabkan perubahan dalam kehidupan seseorang sehingga orang itu terpaksaberadaptasi atau menanggulangi stressor yang timbul. Tujuan umum pada penelitian ini ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…The psychological problems may be in the form of increased anxiety in the general public, patients, medical staff, children, the elderly, and college students. Several studies that have been conducted mentioned the anxiety of students during a pandemic related to various factors including their area of residence, parents' income, living with parents, relatives or acquaintances infected with COVID-19, social support, learning systems, and knowledge about COVID-19 (Kartini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The psychological problems may be in the form of increased anxiety in the general public, patients, medical staff, children, the elderly, and college students. Several studies that have been conducted mentioned the anxiety of students during a pandemic related to various factors including their area of residence, parents' income, living with parents, relatives or acquaintances infected with COVID-19, social support, learning systems, and knowledge about COVID-19 (Kartini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Fungsi fisiologis pada lansia akan mengalami penurunan akibat dari proses degeneratif, hal ini akan menyebabkan sistem imunitas tubuh lansia mulai menurun dan akibatnya lansia rentan terhadap infeksi . (Tinggi et al, 2020) Lansia yang tidak memiliki penyakit kronis merupakan lansia yang tidak menderita penyakit yang lebih dari 6 bulan. Pada penelitian ini kemungkinan lansia mengalami proses degeneratif namun tidak mengalami penurunan kesehatan.…”
Section: A Karakteristik Lansiaunclassified
“…A study by Bourion-Bédès et al (2021) showed 36%, 15.2%, and 9.8% mild, moderate, and severe anxiety among French students (Bourion-Bédès et al, 2021). They were based on a study by Kartini et al (2021), about 15.7% of Haluoleo University students had an anxiety disorder during the outbreak (Kartini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%